The Effect of the Burden on the Quality of Life of Caregivers of People with Parkinson’s Disease - Aleksandra Pytel; Monika Laskowska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2021)
Introduction. Parkinson’s disease is one of the most common neurodegenerative diseases. This condition is progressive in nature. In Europe, Parkinson’s disease is estimated to affect mainly people over the age of 60. It is assumed that around 80–100,000 people in Poland currently suffer from Parkinson’s disease. The disease mainly affects men. Aim. Assessment of the level of burden on caregivers of people with Parkinson’s disease and evaluation of their quality of life. Material and Methods. The study was conducted in the Koło Przyjaciół Ludzi z Chorobą Parkinsona TWK (Friends of People with Parkinson’s Disease TWK Group) in Wrocław and the Leszczyńskie Stowarzyszenie Osób z Chorobami Alzheimera i Parkinsona (Leszno Association of People with Alzheimer’s and Parkinson’s Diseases) in Leszno on a group of 92 Parkinson’s disease patients and their 92 caregivers. The study was conducted using a diagnostic survey method with a self-designed questionnaire and the following standardised instruments for caregivers: the WHOQoL-BREF questionnaire, the CBS caregiver burden scale and the HADS anxiety and depression scale. The present study also used questionnaires addressed to Parkinson’s disease patients: a sociodemographic questionnaire, the PDQ-39 quality of life questionnaire, the Hoehn–Yahr disease stage scale and the Beck depression scale BDI. Results. Analysis of the research material showed that: the quality of life of caregivers in the physical, environmental and psychological domains was significantly better in those providing care for 1–5 years than in those looking after patients for more than 10 years. The author’s own research showed that the overall burden among caregivers was significantly higher when the patient had been ill for more than 5 years than when the patient had been ill for 2–5 years, and it was found that the lower the overall level of quality of life and severity of depressive symptoms among PD patients, the lower the quality of life of their caregivers. On the overall burden scale, 47 of the 92 survey participants (51.09%) experienced a medium level of burden and 24 respondents (26.09%) experienced a high level of burden. In addition, the long duration of the disease leads to a higher burden on caregivers. Conclusions. The difficulties associated with the burden of care for caregivers of people with PD represent a significant clinical, social and also economic problem. Moreover, they significantly reduce the quality of life of caregivers, often taking away the joy of caring for loved ones with Parkinson’s disease. (JNNN 2021;10(4):144–152)